El Retraso Mental Leve y su influencia en la adaptación escolar de los estudiantes de la Escuela “Nuestro Mundo ECO-RÍO” de la ciudad de Riobamba, periodo académico 2014-2015. - Torres Peñafiel, Jhonny Santiago (2016)
It is a common occurrence within the educational context to meet students whit school adjustment; this is determined by poor academic performance difficulty managing their social relationships and problems in the emotional area; being mental retardation a condition of vulnerability to this problem, it has been identified in some children at the Private School “Nuestro Mundo Eco-Rio” of the city of Riobamba, so this investigation is born. A large group of students was determined with school adjustment problems related to some type of cognitive impairment such as Mental Retardation Mild (RML), this situation was checked by applying two psychological reagents, such as the Wechsler Intelligence Scale for Children (WISC) and self reported Multifactor children adaptation Test (TAMAI), results that led to the creation of a Guide of Itervention by Psychopedagogical strategies to improve school adaptation of children with RML, it consists of a manual for curricular adaptations and activities focused on building capacities to personal, social and motor level. The research design used in this thesis was quasi-experimental, as it was developed and applied a Psychopedagogical Guide Strategies; the population consisted of 20 students identified with RML during the academic year 2014-2015 who actively, so that the results contributed significantly to the overall development in students, since it was improved remarkably school adjustment processes optimizing the progress of future roles of the students in the course of their academic and social life.